2010
DOI: 10.4321/s1886-36552010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to medication counselling for people with mental health disorders: a six country study

Abstract: Provision of medication information may improve adherence and prevent medication related problems. People with mental health disorders commonly receive less medication counselling from pharmacists than people with other common long term and persistent disorders.ObjectiveThe objective of this study was to compare and contrast barriers pharmacy students perceive toward providing medication counselling for people with mental health disorders in Australia, Belgium, Estonia, Finland, India and Latvia.MethodsBarrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 60 publications
(79 reference statements)
1
31
0
Order By: Relevance
“…[33][34][35][36] Of the pharmacists who responded to a Canadian study, 24% indicated they learned enough about mental health during their pharmacy training compared to 61% that learned enough about cardiovascular disorders. 33 Pharmacy curricula have instituted changes to circumvent knowledge deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Of the pharmacists who responded to a Canadian study, 24% indicated they learned enough about mental health during their pharmacy training compared to 61% that learned enough about cardiovascular disorders. 33 Pharmacy curricula have instituted changes to circumvent knowledge deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Aaltonen et al 9 mentioned that psychiatric patients receive less medication information from physicians and pharmacists than non-psychiatric patients. Indeed, pharmacists have reported that they lack confidence providing medication information to this particular patient group 9.…”
Section: Discussionmentioning
confidence: 99%
“…treat, a pattern contrasted with practices related to physical illness, and linked to a diminished 330 sense of related competence or interest. 28,36,51,52,72,97 As well, some services might be viewed by 331…”
Section: Confronting Inequities 14mentioning
confidence: 99%
“…Over a third (37.6%, n=35) of the scientific articles 283 considered pharmacists' knowledge levels about marginalized or vulnerable groups as related to 284 equitable care. Findings evidence some knowledge deficits, including an understanding of the 285 origin of mental illness, e.g.,43,48 knowledge regarding the needs/preferences of those with mental 286 illness, 36,43,72 and core competencies and best practices related to service provision for those with 287 mental illness. 28,51,52 Pharmacists' knowledge about the circumstances and needs of those who 288 abuse/ misuse drugs, including prescription or injection street drugs, 26,29,56 and of those with or at 289 risk for HIV/AIDS 34,37,38,46,67 or Hepatitis C is also lacking.…”
Section: Confronting Inequities 13mentioning
confidence: 99%
See 1 more Smart Citation